A Novel Ultrasound Technique Called Saline Infusion SonoPODography to Visualize and Understand the Pouch of Douglas and Posterior Compartment Contents: A Feasibility Study. (15th May 2019) - Leonardi, Mathew; Espada, Mercedes; Lu, Chuan; Stamatopoulos, Nicole; Condous, George
Abstract : Women with infertility are often investigated with saline‐infusion sonohysterography and hysterosalpingo‐contrast‐sonography. The high prevalence of endometriosis in this population also warrants an evaluation with transvaginal ultrasound for deep endometriosis. To minimize investigations, we prospectively evaluated the feasibility of a novel combined ultrasound technique called saline‐infusion sonoPODography. In most patients, the fluid infused to assess the cavity and tubal patency spilled through patent tubes and filled the pouch of Douglas, yielding a "standoff" view of posterior compartment structures, including uterosacral ligaments, rectovaginal septum, and the pouch of Douglas. We believe this improved our ability to evaluate this space.